Isophya sonora, a new bush-cricket species from Eastern Black Sea region of Turkey (Orthoptera: Tettigoniidae; Phaneropterinae) - Sevgi̇li̇, Hasan (Zootaxa, 2020)
Herein I describe Isophya sonora sp. nov. a new bush-cricket species from Trabzon, Northeastern part of Turkey (Black Sea Region). The species is characterized by the shape of the markedly convergent fastigium, distinctly broadened pronotum at metazona, elongate tegmina and large mirror area of left tegmen in the male. The bioacoustic characteristics, and the shape and number of the teeth of stridulatory organs are also different compared to closely related species. The new species is clearly a member of I. zernovi species-group allied with I. bivittata. Both the bioacoustics, and the morphological data, demonstrate the relationships between species of the I. zernovi species-group are as follows: (I. bicarinata + (I. zernovi + I. horon)) + (I. sonora sp. n. + I. bivittata?))) + (I. karadenizensis + I. autumnalis)))).